2003
DOI: 10.1366/00037020360695964
|View full text |Cite
|
Sign up to set email alerts
|

Osteoradionecrosis (ORN) of the Mandible: A Laser Raman Spectroscopic Study

Abstract: Laser Raman spectroscopy has been used in this study to characterize mandibular bone samples from patients who had undergone radiation therapy for oral cancer. The paper discusses spectral changes resulting in osteoradionecrosis (ORN) of the mandibular bone, a serious complication that may occur after radiation therapy. Histopathological studies normally reveal the radiation damage on vascular canals and loss in bone cells, but will not reveal any structural or biochemical changes. All radiation-induced side e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 22 publications
3
44
1
Order By: Relevance
“…Recently studied computational approach of localized tissue mineralization by Berli et al found that a less mineralized bone is situated closer to the surface while a more mature and mineralized bone is buried deeper in the inner cores of the trabeculae [34]. It should also be noted that lipids have characteristic bands around 1442-1444 cm −1 [35]. In the in vivo spectra, there might be overlap of lipid and protein bands close to the −1 band in this study.…”
Section: Resultsmentioning
confidence: 54%
“…Recently studied computational approach of localized tissue mineralization by Berli et al found that a less mineralized bone is situated closer to the surface while a more mature and mineralized bone is buried deeper in the inner cores of the trabeculae [34]. It should also be noted that lipids have characteristic bands around 1442-1444 cm −1 [35]. In the in vivo spectra, there might be overlap of lipid and protein bands close to the −1 band in this study.…”
Section: Resultsmentioning
confidence: 54%
“…Composition changes accompanying osteoradionecrosis of the mandible (induced by radiation therapy for oral cancer) have been interpreted as the result of destruction of vascularity and marrow in the jaw, resulting in loss of lipids and collagen and causing changes in the structure of the bone mineral itself [41]. These composition changes have been detected by Raman spectroscopy in specimens from people who had bone tissue removed as a result of cancer in soft tissue of the jaw.…”
Section: Chemical and Radiologic Insults To Bone Tissuementioning
confidence: 99%
“…At this writing, only the major components of bone have been observed spectroscopically, namely mineral phosphate, carbonate, and matrix collagen. Bone lipids and phospholipids have also been observed [41,57], although they maybe inaccessible as a result of removal during specimen preparation.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted, however, that a specific challenge of applying visible Raman spectroscopy to solid biological tissue is fluorescence interference [53]; this has led to the use of near-IR excitation [54,55,56] and highly sophisticated background subtraction and data analysis techniques [9,57] to mitigate this problem. To help resolve this issue, we have reported recently the first in situ deep ultraviolet Raman spectroscopy measurements on human cortical bone [58], where the use of 244 nm excitation both completely eliminates the fluorescence interference and increases the signal strength of some features from the organic (collagen) phase due to resonance effects.…”
Section: Molecular Scale: Raman Studiesmentioning
confidence: 99%